ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA TOKO SWARNA MART - Adriamal, Indra Putra; Yaakub, Saleh; Ikhsan, Muhammad (LPPM Universitas Muhammadiyah Jambi, 2024)
Swarna Mart Store is a store engaged in the sale of household necessities such asbasic necessities and others. However, in selling so many goods, the sales systemstill uses the manual method. The purpose of this study is to analyze and design asales information system, including facilitating product sales, recording salestransactions, searching for goods and making reports. System modeling uses UML(Unified Modeling Language) which consists of Use Case Diagrams, ActivityDiagrams and Class Diagrams, with a design limited to a prototype. This studyproduced a prototype sales information system that is able to help the CenhsinStreet store in carrying out operational activities. In further development, it ishoped that this sales information system can have a more attractive appearance.